Comparison of Hemodialysis Service Cost Effectiveness Using Activity-Based Cost Approach with Hospital Cost and Cost Recovery Rate in Regional Public Hospital IA Moeis Samarinda - Hasan, Hismawati; Ratno Adrianto; Ike Anggraeni (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
The determination of service rates in hospitals is often not based on unit cost calculations, but rather on fixed rates used by other hospitals for practicality and ease of implementation. This leads to the problem of differences between INA-CBGs rates and hospital rates in the era of the National Health Insurance (JKN). The study aimed to determine the unit cost of Hemodialysis services using the Activity-Based Costing method, and compare with hospital rates and INA CBGs, and calculate the recovery rate cost. This is a descriptive research study employing a case study approach. This research was conducted to describe the current condition of the hospital costing system, revealing the cost structure and calculation of service unit costs using the Activity-Based Costing method. The Hospital's financial transaction reports of 2023 were used as a data source. Data is grouped based on fixed costs, semi-variable costs, and variable costs, and then translated into direct costs and overhead costs to calculate the unit costs of hemodialysis. The results of the Hemodialysis unit cost calculation were compared with hospital rates and INA CBGs. The cost recovery rate was then calculated. The study results showed that the unit cost of Hemodialysis, calculated using the Activity-Based Costing method, was Rp1,364,257. The comparison result was that the unit cost was higher than the hospital rate (86%) and also than the INA CBGs rate (61%). The results of the cost recovery rate (CRR) calculation are still below 100%. Influencing factors include direct costs, overhead costs, and the number of actions.